Pengembangan Leaflet Digital Tema Makananku Kesehatanku untuk Menumbuhkan Kemampuan Berpikir KritisSiswa SMP Kelas VIII - Nurdayanti Nurdayanti; Dwi Indah Suryani; R. Ahmad Zaky El Islami (UNIB Press, 2023)
According to the results of interviews conducted at junior high schools in the Lebak area, learning activities aimed at developing students' critical thinking skills have not been carried out properly. For this reason, teaching resources that can be used are digital leaflet teaching materials. This study animed to obtain the feasibility and legibility of digital leaflets with the topic